Dysfunction of the Gut Microbiome and its Onset Progression of Chronic and Mental Health Disorders - Ayesha Ameen, Anam Amir, Muhammad Nauman Aziz, Asma Irshad, Maryam, Shehr Hayat, Hassan Raza, Athar Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
The gut microbiome is a complex community of microbes that inhabits the gastrointestinal tract and plays a crucial role in maintaining human health. Recent research has demonstrated that gut dysbiosis, or an imbalance in the microbiome, is associated with the development of various chronic and psychiatric diseases, such as obesity, cardiovascular disease, and depression. The mechanisms by which gut dysbiosis contributes to disease development involve alterations in the gut-brain axis, gut-liver axis, and gut-immune system interactions. Studies have shown that gut microbiome dysbiosis can cause up-regulation of certain pathways involved in disease development, including systemic inflammation, oxidative stress, and intestinal permeability. Additionally, gut dysbiosis has been linked to alterations in neurotransmitter synthesis and gut hormone secretion, which can influence the brain and contribute to mood and cognitive disorders. Further research is necessary to fully comprehend the mechanisms underlying this relationship and to develop effective strategies for the prevention and treatment of chronic and psychiatric diseases. In conclusion, gut microbiome dysbiosis plays a critical role in the up-regulation and development of chronic and psychiatric diseases and is an area of growing interest in the scientific community. Further investigation is needed to fully understand the mechanisms underlying this relationship and to develop effective treatments and interventions. Keywords: Gut microbiome , chronic, mental health, dysfunction